The design of small-molecule prodrugs and activatable phototherapeutics for cancer therapy - Han, Hai-Hao; Wang, Han-Min; Jangili, Paramesh; Li, Mingle; Wu, Luling; Zang, Yi; Sedgwick, Adam C; Li, Jia; He, Xiao-Peng; James, Tony D; Kim, Jong Seung (Chemical Society reviews, 2023)
Cancer remains as one of the most significant health problems, with approximately 19 million people diagnosed worldwide each year. Chemotherapy is a routinely used method to treat cancer patients. However, current treatment options lack the appropriate selectivity for cancer cells, are prone to resistance mechanisms, and are plagued with dose-limiting toxicities. As such, researchers have devoted their attention to developing prodrug-based strategies that have the potential to overcome these limitations. This tutorial review highlights recently developed prodrug strategies for cancer therapy. Prodrug examples that provide an integrated diagnostic (fluorescent, photoacoustic, and magnetic resonance imaging) response, which are referred to as theranostics, are also discussed. Owing to the non-invasive nature of light (and X-rays), we have discussed external excitation prodrug strategies as well as examples of activatable photosensitizers that enhance the precision of photodynamic therapy/photothermal therapy. Activatable photosensitizers/photothermal agents can be seen as analogous to prodrugs, with their phototherapeutic properties at a specific wavelength activated in the presence of disease-related biomarkers. We discuss each design strategy and illustrate the importance of targeting biomarkers specific to the tumour microenvironment and biomarkers that are known to be overexpressed within cancer cells. Moreover, we discuss the advantages of each approach and highlight their inherent limitations. We hope in doing so, the reader will appreciate the current challenges and available opportunities in the field and inspire subsequent generations to pursue this crucial area of cancer research. This tutorial review provides a general overview for the design of prodrugs and activatable phototherapeutics which enables the development of improved therapies.